2016
DOI: 10.1128/aem.00133-16
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Stability of Swine and Human Pandemic Influenza Viruses in Water under Variable Conditions of Temperature, Salinity, and pH

Abstract: The movement of influenza A viruses (IAVs) from wild bird reservoirs to domestic animals and humans is well established, but the transmission mechanisms that facilitate efficient movement across and within these host populations are not fully defined. Although predominant routes of transmission vary between host populations, the extent of environmental stability needed for efficient IAV transmission also may vary. Because of this, we hypothesized that virus stability would differ in response to varied host-rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 33 publications
0
23
0
1
Order By: Relevance
“…To date, many studies have evaluated the environmental factors (temperature, salinity, and pH) that influence the stability of different AIVs under variable conditions. Overall, the persistence of AIVs was negatively associated with the temperature and acidity of the environment, and it has been suggested that AIVs remains infective for the longest time between a pH of 7.2 and 8.4 at low temperature 46 , 48 , 49 . In line with previous studies on viral persistence, our study also showed that both HH179/H7N7 and CH1228/H7N7 were more stable under the condition of near-neutral pH (7.2) and cold temperature (4 °C) than under other conditions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, many studies have evaluated the environmental factors (temperature, salinity, and pH) that influence the stability of different AIVs under variable conditions. Overall, the persistence of AIVs was negatively associated with the temperature and acidity of the environment, and it has been suggested that AIVs remains infective for the longest time between a pH of 7.2 and 8.4 at low temperature 46 , 48 , 49 . In line with previous studies on viral persistence, our study also showed that both HH179/H7N7 and CH1228/H7N7 were more stable under the condition of near-neutral pH (7.2) and cold temperature (4 °C) than under other conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In line with previous studies on viral persistence, our study also showed that both HH179/H7N7 and CH1228/H7N7 were more stable under the condition of near-neutral pH (7.2) and cold temperature (4 °C) than under other conditions. In addition, Poulson et al 46 . evaluated the ability of eight swine (H1N1 and H3N2) and six human (H1N1 and H3N2) strains to remain infective under various pH, temperature, and salinity conditions.…”
Section: Discussionmentioning
confidence: 99%
“…At pH 7.0, the titers of both viruses dropped from approximately 5.7 log 10 to 1.7 log 10 TCID 50 /mL over a period of 72 h. When virus aliquots were incubated at pH 6.4, the titer of Y17H virus decayed at an accelerated rate compared to that of WT virus. The 90% reduction time (Rt value) is the time required for a 90% (1 log 10 ) decrease in the viral titer (56). At pH 7.0, the Rt values for the WT and Y17H viruses were similar (21.7 ± 1.5 h and 20.4 ± 2.1 h, respectively); however, at pH 6.4, the Rt values for the WT and Y17H viruses were 26.6 ± 1.8 h and 7.4 ± 0.6 h, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular environments with acidic pH (pH <6.6), warmer temperature, and/or higher salinity decrease the environmental persistence of IAVs (56, 60). Environmental stability can also be decreased by destabilizing HA mutations (41), i.e., those that increase the pH at which the HA protein becomes activated to undergo irreversible structural changes (16, 30).…”
Section: Discussionmentioning
confidence: 99%
“…A 20-fold reduction in titer of feline calicivirus (FCV), a nonenveloped RNA virus, was reported when introduced into artificial seawater (18). In contrast to nonenveloped RNA virus, lower survival of human and swine influenza viruses (enveloped RNA viruses) was reported when the virus was incubated in saline solutions up to 30 ppt salinity (19). Similarly, survival of avian influenza virus was inhibited when the virus was incubated in Ͼ25 ppt saline (20).…”
Section: Discussionmentioning
confidence: 99%